PENGUKURAN KINERJA: SEBUAH PENGAKUAN DAN PENGUKURAN PENDAPATAN PERUSAHAAN - Rizki Arvita (JCA (Jurnal Cendekia Akuntansi), 2022)
This study aims to determine whether the method of recognizing and measuring income according to PSAK No. 23 has been applied by pest management service companies in Surabaya. The research method used is qualitative by using case studies to describe how pest management companies measure income using the recognition and measurement method of income according to PSAK No. 23. Research on Surabaya's pest management service providers is done using the accrual basis method. By selling services that have been recorded as revenue and are certain to be realized, the study findings show that the firm recognizes revenue in line with PSAK No. 23, financial accounting rules. The amount of money collected from clients less costs is used to calculate revenue. The fair worth of the advantages that the firm has got or will get is used to calculate income. Keywords: Recognition, Measurement, Revenue, PSAK No. 23